2015
DOI: 10.1021/jacs.5b06737
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-Conjugated Pyrazines as Molecularly Tunable Heterogeneous Electrocatalysts

Abstract: Condensation of ortho--phenylenediamine deriv--atives with ortho--quinone moieties at edge planes of graphitic carbon generates graphite--conjugated pyrazines (GCPs) that are active for oxygen reduction electrocatalysis in alkaline aqueous electrolyte. Catalytic rates of oxygen reduction are positively correlated with the electrophilicity of the active site pyrazine unit, and can be tuned by over 70 fold by appending electron--withdrawing substituents to the phenylenediamine precursors. Discrete molecular anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 37 publications
11
128
0
Order By: Relevance
“…For NRR, several molecular catalysts, such as Fe‐, Co‐ and Mo‐nitride complexes, have been prepared, where the MN x moieties serve as the active centers ( Figure a). However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts . Among heterogeneous catalysts, N–G‐supported SACs possess similar active centers to that of the molecular catalysts for NRR (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For NRR, several molecular catalysts, such as Fe‐, Co‐ and Mo‐nitride complexes, have been prepared, where the MN x moieties serve as the active centers ( Figure a). However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts . Among heterogeneous catalysts, N–G‐supported SACs possess similar active centers to that of the molecular catalysts for NRR (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts. [48,49] Among heterogeneous catalysts, N-G-supported SACs possess similar active centers to that of the molecular catalysts for NRR ( Figure 1b). Therefore, investigation on the catalytic activity of N-G supported SACs for NRR is of great importance.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology is similar to our previous report and full experimental details of electrode preparation are provided in the SI. 45 To examine the electrokinetic profile of these modified surfaces for ORR, we collected potentiostatic current-potential (Tafel) data across a range of potentials (0.83 -0.65 V; unless otherwise stated, all potentials are reported versus the reversible hydrogen electrode, RHE) spanning the catalytic wave, which correspond to overpotentials ranging from 0.40 to 0.58 V. All data were collected with electrode rotation at 2000 rpm to minimize transport limitations. Data at higher overpotentials were also explicitly corrected for residual transport limitations by extrapolating Koutecky-Levich (KL) plots of the reciprocal of the current density, j −1 , versus the reciprocal square root of the rotation rate, ω −1/2 , to the yintercept, corresponding to infinite rotation rate, to determine the activation-controlled current density ( Figure S1).…”
Section: Electrochemical Kinetics Of N + -Gccsmentioning
confidence: 99%
“…We have shown that this functionalization method generates graphite-conjugated catalysts (GCCs) that display high activity for the ORR in alkaline aqueous media, and that the activity of these GCCs is sensitive to the structure of the molecular fragment incorporated. 45,48 Our initial synthetic studies of structure-activity correlations on GCCs identified carbon surfaces treated with aryl-pyridinium-substituted diamines, dubbed N + -GCCs, to be particularly active for the ORR (Scheme 1). 45 With well-defined catalytic sites and appreciable activity, N + -GCCs are an ideal platform for detailed experimental investigations of the kinetics of ORR catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation